An evaluation of optimal sized second-life electric vehicle batteries improving technical, economic, and environmental effects of hybrid power systems - Terkes, Musa; Demirci, Alpaslan; Gokalp, Erdin (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
Electric vehicle (EV) batteries provide energy and power sufficiently until their capacity degradation reaches 80%. Afterward, EV batteries need to remove due to their insufficient power and energy capacity to satisfy the range and speed requirements. Increasing EV sales means numerous second-life batteries (SLB) will be available for second-use applications. Besides the price and capacity differences of SLB, technical properties such as depth of discharge (DOD), temperature, and cycle life will directly affect the performance. This study comprehensively examines SLB feasibility, focusing on the technical and financial uncertainties of SLBs in stationary energy storage applications. In addition, the contribution of SLB to the marginal cost-revenue balance is optimized by considering various operating criteria and four different battery aging sub-models. The remaining capacity and DOD effects were analyzed, and break-even points were determined. Sensitivity analyses also assess the carbon tax and the performance of SLB in different climatic zones. Finally, the accuracy of technical, economic, and environmental performance has been increased with multi-year sensitivity analysis. According to optimal results, SLB could increase energy efficiency up to 14% with 80% capacity and under 80% DOD. It has also been found that if the SLB cost is less than 57% of the fresh battery (FB), the same system will reach the break-even point. Thanks to the carbon tax, SLB reduced discount payback for up to 3 years, increased RF by up to 5%, and improved state of health (SOH) by 13%, giving sustainable environmental and economic results.
Keywords: Hybrid power system; Electric vehicle; Renewable energy; Second -life battery; Carbon tax; SOLAR PHOTOVOLTAICS; ENERGY; LIFE; IMPACTS; LITHIUM; Thermodynamics; Energy & Fuels; Mechanics